Pengembangan Usaha Kuliner Rusmiati Di Desa Sambirejo Timur Kecamatan Percut Sei Tuan - Yul Ifda Tanjung; Irham Ramadhani; Fitrawaty Fitrawaty; Nelson Tarigan (LPPM UNINUS, 2021)
This community service activity was carried out in Sambirejo Timur Village, Percut Sei Tuan District with culinary business partner Rusmiati. The problems faced by partners are consumer demand that is not following production capacity because production is still carried out manually, the lack of partner knowledge about attractive product packaging designs, product halal certification processes, marketing alternatives, and preparation of financial reports. These problems make partner businesses not develop and experience a decline, both in the fields of production and marketing. The methods implemented in this service activity are in the form of education, training, socialization, and mentoring. This method is carried out in the form of training on how to use appropriate technology tools, namely the use of dough printing machines and product packaging tools, training and designing packaging designs that are more attractive, and tidy so that partner products are more durable, socialization and assistance for standardization of the production process including the selection of raw materials, structuring the production space, making work standards to assisting partners in completing LPPOM MUI halal certification application documents as well as implementing education and training on financial accounting and business management and marketing through online store applications by utilizing IT.